2018
DOI: 10.3847/1538-4357/aadf36
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectrification of KCl and ZnS Particles in Approximated Exoplanet Environments

Abstract: When mobilized, granular materials become charged as grains undergo collisions and frictional interactions. On Earth, this process, known as triboelectrification, has been recognized in volcanic plumes and sandstorms. Yet, frictional charging almost certainly exists on other worlds, both in our own Solar System (such as Mars, the Moon, and Venus) and exosolar planets. Indeed, observations suggest that numerous planets in the galaxy are enshrouded by optically-thick clouds or hazes. Triboelectric charging withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…The study of cosmic dust charging has a long history (Jung 1937;Corlin 1938;Spitzer 1941;Watson 1972;Feuerbacher et al 1973) and resulted in general understanding of main charging mechanisms acting in the interstellar medium (see reviews by Goertz (1989); Mendis & Rosenberg (1994) ;Fortov et al (2005) and short summary by Weingartner (2004)). These mechanisms include photoelectric effect (Bakes & Tielens 1994;Weingartner & Draine 2001), plasma charging (Draine & Sutin 1987), secondary electron emission (Draine & Salpeter 1979;Shchekinov 2007), triboelectric charging 1 (Poppe et al 2000;Desch & Cuzzi 2000;Marshall et al 2005;Singh & Mazza 2018;Harper et al 2018) and thermionic emission (Lefevre 1975). In varying external conditions the non-equilibrium grain charging should be considered and may affect dust evolution (Corlin 1938;Horanyi & Goertz 1990;Pedersen & Gómez de Castro 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The study of cosmic dust charging has a long history (Jung 1937;Corlin 1938;Spitzer 1941;Watson 1972;Feuerbacher et al 1973) and resulted in general understanding of main charging mechanisms acting in the interstellar medium (see reviews by Goertz (1989); Mendis & Rosenberg (1994) ;Fortov et al (2005) and short summary by Weingartner (2004)). These mechanisms include photoelectric effect (Bakes & Tielens 1994;Weingartner & Draine 2001), plasma charging (Draine & Sutin 1987), secondary electron emission (Draine & Salpeter 1979;Shchekinov 2007), triboelectric charging 1 (Poppe et al 2000;Desch & Cuzzi 2000;Marshall et al 2005;Singh & Mazza 2018;Harper et al 2018) and thermionic emission (Lefevre 1975). In varying external conditions the non-equilibrium grain charging should be considered and may affect dust evolution (Corlin 1938;Horanyi & Goertz 1990;Pedersen & Gómez de Castro 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dusty or complex plasmas, consisting of microscopic particles immersed in a weakly ionized gas, are ubiquitous in the natural universe and play important roles in man-made systems [1][2][3][4][5][6]. When exposed to a plasma environment, particles gain charge by collecting discrete ions and electrons on their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A number of electrification mechanisms have been invoked to explain electrostatic processes in jets and plumes, including fragmentation charging (James et al, 2000;Méndez Harper et al, 2015), triboelectric charging (Cimarelli et al, 2014;Houghton et al, 2013;Méndez Harper & Dufek, 2016;, charging arising from the decay of radioactive compounds in ash (Houghton et al, 2013), and mechanisms comparable to those thought to operate in thunderclouds (Mather & Harrison, 2006;Nicora et al, 2013). Triboelectrification-referring collectively to the electrification arising from frictional or collisional interactions between two or more surfaces-has been recognized since antiquity (Iversen & Lacks, 2012) and has been detected or inferred to exist in many of natural granular systems (Dou & Xie, 2017;Fabian et al, 2001;Farrell et al, 2004;Forward et al, 2009bForward et al, , 2009dHarrison et al, 2016;Helling et al, 2013;Hodosán et al, 2016;, 2018bSternovsky et al, 2002). Carefully controlled experimental studies have shown that volcanic ash readily charges triboelectrically (Hatakeyama & Uchikawa, 1951;Houghton et al, 2013;James et al, 2000;Méndez Harper & Dufek, 2016;.…”
Section: Introductionmentioning
confidence: 99%